GIANT LEFT ATRIUM WITH MECHANICAL MITRAL PROSTHESIS, SMALL PARAVALVULAR LEAK AND DISLOCATED PACEMAKER ELECTRODE - Piotr J. Stryjewski; Agnieszka Kuczaj; Jadwiga Nessler; Ewa Nowalany-Kozielska (Российский кардиологический журнал, 2015)
Giant left atrium (GLA) is defined as those measuring larger than 8 cm and are typically found in patients who have rheumatic mitral valve disease with severe regurgitation. GLA is a rare condition, with a reported incidence of 0,3%.The patient usually presents with complaints of shortness of breath and/or dysphagia. The correct diagnosis of GLA is at times not possible through the routine chest roentgenogram and may require echocardiography, computerized tomography or cardiac MRI to reach a diagnosis. GLA is associated with complications such as heart failure, valvular heart disease, dislocations of electrode. Patients with GLA are candidates for surgical/catheter interventional treatment at any age.